2002
DOI: 10.1097/00006250-200207000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Uterine Polyps and Leiomyomata

Abstract: OBJECTIVE:To estimate the incidence and regression rates of uterine leiomyomata and polyps in a cohort of asymptomatic, premenopausal women. METHODS:Saline infusion sonography was performed twice, 2.5 years apart, in a cohort of 64 initially asymptomatic women. Subjects completed a questionnaire that assessed the development of abnormal uterine bleeding. RESULTS:The mean age of women (at second ultrasound) was 44 years. In four of seven women with polyps at the original ultrasound, their polyps regressed. Poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 13 publications
6
88
0
10
Order By: Relevance
“…A remarkable finding in our study was that polyps were more frequent in women without AUB compared to women with AUB; 62 % of women with polyps were asymptomatic. The incidentally discovered polyps were reported to be 20-46.2 % [13,16]. On the other hand, Dreisler et al [17] found that the prevalence of uterine polyps among women without AUB was up to 82 % when women with myomas were excluded from analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A remarkable finding in our study was that polyps were more frequent in women without AUB compared to women with AUB; 62 % of women with polyps were asymptomatic. The incidentally discovered polyps were reported to be 20-46.2 % [13,16]. On the other hand, Dreisler et al [17] found that the prevalence of uterine polyps among women without AUB was up to 82 % when women with myomas were excluded from analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, no fibroids were seen that regressed during their observations [22]. The disappearance or shrinking seen in other studies [20] may be caused by the imprecise nature of ultrasound examinations, where a fibroid could be incorrectly mapped or other features of the myometrium, such as a myometrial contraction, may be incorrectly scored as a fibroid, which might then later be seen to disappear.…”
Section: Incidence At Different Ages and Progressionmentioning
confidence: 92%
“…Advancing age increases the risk for fibroids many fold, and mirrors the understanding of the biologic development of fibroids: most grow in time and are expected to be diagnosed in greater numbers in older cohorts. A small sample of patients who had their fibroids followed-up ultrasonographically [20] saw an average growth of 1.2 cm in 2.5 years. The chance of being diagnosed with fibroids increases with age until about 50 years and then declines sharply [8,11].…”
Section: Incidence At Different Ages and Progressionmentioning
confidence: 99%
“…19,20 Whether fibroids are symptomatic or not depends primarily on their size and on their position in relation to the uterine cavity. 21 Although the definitive management of gynecological symptoms attributable to uterine fibroids is surgical removal, many women decline surgery or prefer to pursue medical management. The natural history of fibroids is poorly understood, which makes it difficult to advise asymptomatic women with fibroids on the risk of developing clinical symptoms in the future.…”
Section: Discussionmentioning
confidence: 99%